A study on the relationship between job satisfaction and affective commitment among support staff in selected public sector departments at Jalan Sultan Ismail, Kuala Terengganu, Terengganu / Nur Fakhriah Azmi - Azmi, Nur Fakhriah (2016)
The purpose of this research was to investigate the correlation between job satisfaction and affective commitment among support staff in selected public sector departments at Jalan Sultan Ismail, Kuala Terengganu, Terengganu. This correlational study used a stratified disproportionate sampling technique and the sample size was determined using Krejcie and Morgan (1970). Survey questionnaires were distributed to 123 respondents who worked as support staff and yield 80% response rate. Majority of the respondents were female, aged 41 to 50 years old and from grade C. Many of them has more than 20 years of experience. The findings showed that there was a strong relationship between job satisfaction and affective commitment (r= 0.86, p=0.00). Moreover, the correlation was also significant as a result for salary (1=0.678, p=0.00), fringe benefit (r=0.665, p=0.00) and promotion (r=0.514, p=0.00). The value of R-Square showed that 54.5% of the variance in job satisfaction can be predicted from the variables of salary, fringe benefit and promotion. The multiple regression model produced F (3, 95) =0.00, p<.05. The result also indicated no correlation between length of service and affective commitment. It is recommended that managers should improve the affective commitment of the employee, improve employee's welfare, encourage cooperation among employees and improve decision making skills. Future research should study on other industry in Malaysia and include broader scope of respondents including top management, in order to gain more comprehensive result.